Harvesting of energy from Human Walking with a piezoelectric transducer to supply a medical instrument - Mostafa Fakhar; Amin Mahnam; Mehdi Edrisi (Vesnu Publications, 2013)
Abstract Introduction: Nowadays, the advanced technology of designing electronic circuits in very small size and with very low power consumption has led to development of wearable and implantable medical devices. However, the electronic circuits need power supply that is usually provided by relatively large and heavy batteries. The discharged batteries have to replaced or recharged for long time operation of electronic circuits. A new promising approach to overcome these limitations is harvesting the required power from the human body itself. Materials and Methods: In this paper, a harvesting system which implements a high performance piezoelectric transducer in the shoe was developed and evaluated for supplying the power required by a basic electronic circuit as a model of a wearable medical device. Results: The developed system was able to harvest 0.8mw of steady power with the use of only one piezoelectric transducer. The power was used to supply a basic micro-controller based electronic system steadily without the need for any batteries. Conclusion: The results demonstrate that low power monitoring or rehabilitation instruments may be supplied without batteries by harvesting the available energy in the walking process. Keywords: Energy harvesting, Human walking, Piezoelectric Transducer, Wearable Medical Devices